2008
DOI: 10.1183/09031936.00090407
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos induces doxorubicin resistance in MM98 mesothelioma cells via HIF-1 

Abstract: Human malignant mesothelioma (HMM), which is strongly related to asbestos exposure, exhibits high resistance to many anticancer drugs. Asbestos fibre deposition in the lung may cause hypoxia and iron chelation at the fibre surface. Hypoxia-inducible factor (HIF)-1a, which is upregulated by a decreased availability of oxygen and iron, controls the expression of membrane transporters, such as P-glycoprotein (Pgp), which actively extrude the anticancer drugs. The present study aimed to assess whether asbestos may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Tests for PIK3CA and K-RAS mutations were performed using a similar method. Exons 9 (codons 532-554) and 20 (codons 1011-1062) for examined PIK3CA mutations, and codons 12, 13 and 61 were examined for KRAS mutations 7 . PTEN loss was assessed using immunohistochemistry 12 (monoclonal mouse anti-human PTEN, clone 6H2.1, Dako®, Denmark) 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tests for PIK3CA and K-RAS mutations were performed using a similar method. Exons 9 (codons 532-554) and 20 (codons 1011-1062) for examined PIK3CA mutations, and codons 12, 13 and 61 were examined for KRAS mutations 7 . PTEN loss was assessed using immunohistochemistry 12 (monoclonal mouse anti-human PTEN, clone 6H2.1, Dako®, Denmark) 12 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, up regulation of the transcription factor hypoxia-inducible factor alpha (HIF-1α), with subsequent increases in the production of proteins that promote angiogenesis, anaerobic metabolism and other cellular survival pathways, has been demonstrated as an important mechanism of anthracycline resistance 5-7 .…”
Section: Introductionmentioning
confidence: 99%
“…Improved, but modest, response rates have been achieved with combination therapy of cisplatin with gemcitabine, vinorelbine, ironotecan, raltitrexed or vinflunine. The resilient, aggressive nature of this malignancy is attributed to TRAIL resistance resulting from elevated baseline levels of known pro-survival effectors including FLIP L ,5 HIF-1α,6 BCL-X L ,7,8 IAP-1,9,10 survivin,10,11 XIAP,10 MCL-1 L , p21,12 PECAM-1,13 HSP70 and the stem cell factor (SCF)/c-Kit/Slug pathway 14. In addition to these resistance patterns, MPM human cell lines have also been demonstrated to have high levels of c-src15 and AKT pathway activity.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of p-glycoprotein was up-regulated at low pH conditions in EMT6 cells and prostate cancer cells (Thews et al, 2006 ). This upregulation of p-glycoprotein is partially dependent on HIF-1 (Riganti et al, 2008) and extracellular low pH has been reported to induce HIF-1 (Mekhall et al, 2004). So, this mechanism might contribute to the pHdependent loss of cytotoxicity as shown in Fig.1, in addition to the possibility derived from its weakly basic conformation (Raghunand et al, 1999).…”
Section: Doxorubicin and Daunorubicinmentioning
confidence: 95%